INSPIRATION FROM JESUIT AND MONTESSORI EDUCATION IN THE DESIGN OF AN INCLUSIVE PRIMARY SCHO - Kurniastuti, Irine; Winarti, Eny; Agus Arswimba, Bernardinus; Heri Widodo, Yohanes (JPI (Jurnal Pendidikan Inklusi), 2024)
There have been many calls for concern for students with special needs. However, many schools under the Catholic Foundation are still experiencing obstacles in providing adequate learning accommodations for them. This research seeks to make a design proposal for a Guide to Celebrating Diversity in regular schools which are in the process of becoming inclusive schools. The design was prepared based on a needs analysis result. The design was based on literature searches and good practices in various inclusive schools and the basics of Jesuit and Montessori education. The designs prepared are given input by expert practitioners and submitted to teachers at schools to get input. This design is very likely to be used by school stakeholders. The main principle that needs to be considered is the Foundation's policy regarding the preparation of human resources, acceptance of new students, curriculum accommodation, the prepared environment, and funding. Keywords: inclusive, Jesuit education, Montessori method